Opportunities, challenges and recommendations of non-traditional placements for occupational therapy students: a review of the literature - Dzalani Harun; Tan Eileen; Hanif Farhan Mohd Rasdi (Pusat Perkembangan Pelajar ,U.K.M, 2003)
Many studies have been conducted to test the effectiveness and functionality of non-traditional placements in place of traditional clinical placements. This review aims to explore the opportunities and challenges in conducting a non-traditional placement among occupational therapy students and provide recommendations to improve the practice. The EBSCOhost search engine was used to search through three databases for articles ranging within 10 years. A secondary search was done and several additional references were found through other sources. A total of 10 articles were included in this review. The review found that many opportunities could be gained from nontraditional placements in terms of professional development, personal growth and potential role development. The challenges arise in the development of core clinical and professional skills, supervisory model and implementation of the placement. In conclusion, occupational therapy students can benefit from non-traditional placement despite the challenges in its implementation. Careful planning and proper strategies are important to mitigate challenges and thus enhance the efficiency of a non-traditional placement in students’ clinical placement.